Al stabilized TiC twinning platelets. Issue 9 (23rd April 2014) - Zhang, Hui; Wang, Xiaohui; Li, Zhaojin; Zhou, Yanchun
Abstract: Abstract : Titanium carbide (TiC) twins are believed to be extremely unstable because of their high twin boundary energy. Here, we report that TiC twins are always presented in platelets with dimensions of 2–3 μm in length and less than 300 nm in width. In-depth microstructural characterizations by high-resolution transmission electron microscopy demonstrate that Al atoms at the twin boundary play a decisive role in stabilizing TiC twins. With different amounts of Al, perfect and defective TiC twins are formed. For perfect twins, three types of twin boundaries can be formed depending on the amount of remaining Al at the twin boundary. With inadequate Al, the TiC twins become defective with certain degrees of deviation from the perfect twin orientation. Based on a detailed analysis of the microstructure of the twin boundaries, a mechanism for the formation and stabilization of TiC twins is proposed.